Electron spin resonance studies of 53Cr3+ and VO2+ ions in A1C13.6H2O. - Pack, Kenneth. (University of Ottawa (Canada), 1975)
Electron spin resonance (ESR) studies are reported for Cr3+ and VO2+ in AlCl3.6H2O. Electron-nuclear double resonance (ENDOR) studies are reported for the isotope 53Cr 3+ in AlCl3.6H2O. All the microwave measurements were done at X-band microwave frequencies (∼ 9.4 GHZ). The VO2+ study was done at room temperature and it shows that these are two different orientations of the Al3+.6H2O complexes per unit cell. The VO2+.5H2O complexes associated with the two types of Al3+.6H2O complexes are rotated with respect to each other by an angle 33° +/- 3° in the plane perpendicular to the crystal c axis. The Cr3+ ESR measurements were done at four temperatures between room and liquid helium temperature, while the ENDOR of 53Cr3+ was done at liquid helium temperature. The Cr3+ studies show that the sign of the spin Hamiltonian zero-field splitting parameter D is negative, indicating that the Cr3+.6H2O magnetic complexes are trigonally compressed in AlCl3.6H2O. A comparison is made between the spin Hamiltonian parameter for 53Cr3+ impurities in several hydrated crystals and it is found that a purely static crystal field model does not satisfactorily explain the experimental results. When the VO2+. spin Hamiltonian parameters are also included in the comparison it is possible to make conclusions regarding the relative susceptibility of the various Al3+.6H2O complexes to distortion upon impurity doping. In particular it is concluded that the complexes in CsAl alum are more susceptible to distortion than are those in AlCl 3.6H2O.
Keywords: Physics, Nuclear.